ХАЛЫҚ ДӨРЕТИЎШИЛИГИНДЕГИ АҚЫЛ-ТӘРБИЯСЫ АРҚАЛЫ ЖАСЛАРДА МИЛЛИЙ ИДЕЯНЫ ҚӘЛИПЛЕСТИРИӮ МӘСЕЛЕЛЕРИ - Тилегенов, А.Т. (SCIENCE and SOCIETY, 2024)
This article examines the issues of forming a national idea among young people through intellectual education through folk art. The importance of mental education in the spiritual development of a person is also discussed.
Keywords: intellectual education; folk oral creativity; youth; national idea; formation; folk pedagogy; experience; labor; evolutionary process; folk pedagogy in the family; material and spiritual benefits